N. F. S. Grundtvigs bopæle (adresser) i København - Johansen, Steen (Grundtvig-Studier, 1963)
Places at which N. F. S. Grundtvig stayed in Copenhagen. II. 1822-1872. By Steen Johansen. The essay (continuing a treatment of the same subject for the years to 1821 in Grundtvig-Studier i960, 54-65) provides exact information about the places at which Grundtvig stayed in Copenhagen from 1822 to 1872. The information has been derived chiefly from private letters, census-papers, memoirs, and newspapers. Besides informing us about Grundtvig’s dwellingplaces the essay helps enlighten some obscure aspects af Grundtvig’s private life. We learn e. g., that later in life the choice of his addresses was most frequently made by other persons (esp. his second, and later his third wife), and that restless and quiet periods of his literary life correspond to frequent or less frequent changes of dwelling-place. The essay concludes with a complete list of Grundtvig’s addresses in Copenhagen 1800-1872.